2021
DOI: 10.1177/17571774211033351
|View full text |Cite
|
Sign up to set email alerts
|

What are the predictors of hand hygiene compliance in the intensive care unit? A cross-sectional observational study

Abstract: Background: Although appropriate hand hygiene (HH) practices are recognised as the most effective preventative strategy for infection, adherence is suboptimal. Previous studies in intensive care units (ICUs) have found differences in HH compliance between those moments that protect the patient, and those that protect the healthcare provider. However, such studies did not control for other variables known to impact HH compliance. Aim: To examine HH among healthcare workers (HCWs) in ICU settings, and identify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Healthcare workers frequently contact patients, making it easy for microorganisms to be transmitted through their hands ( 9 ). In intensive care units (ICUs), the problem is more critical due to a higher infection rate than in other wards, as well as high-risk patients due to multiple injuries, low awareness, and weak prevention mechanisms ( 10 ). Hand hygiene compliance has improved patient health and safety and decreased complications, hospital stays, and death risks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare workers frequently contact patients, making it easy for microorganisms to be transmitted through their hands ( 9 ). In intensive care units (ICUs), the problem is more critical due to a higher infection rate than in other wards, as well as high-risk patients due to multiple injuries, low awareness, and weak prevention mechanisms ( 10 ). Hand hygiene compliance has improved patient health and safety and decreased complications, hospital stays, and death risks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, before contacting patients, healthcare workers exhibit a lower level of compliance than after contacting patients ( 16 ). Furthermore, another study found that hand hygiene is more commonly practiced during night shifts than morning shifts and patient protection than self-protection ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These exercises stimulate employee attitude and behavior changes while also advancing their knowledge and abilities. [30]. For instance, enhancing moms' education while considering current viewpoints might result in favorable modifications [31].…”
Section: Knowledge Of the Training Participantsmentioning
confidence: 99%
“…(6) Podem fornecer estimativas das taxas de conformidade durante todos os turnos, todos os dias da semana e eventualmente categorizar conforme os diferentes profissionais. (6,47,48) Esses sistemas facilitam análise do efeito em estimar taxas de aderência de várias intervenções, como estratégias de feedback, programas como "positive deviance", efeitos da duração do observador humano e a extensão do efeito Hawthorne. (6) Apesar dos sistemas de monitoramento poderem aumentar a aderência à higiene das mãos, não podemos esquecer que os fatores humanos podem desempenhar um papel importante nesse processo.…”
Section: Observação Eletrônica Com Contadores Eletrônicos De Dispensadorunclassified